Preparation method of mesoporous material, foaming aggregate, lithium slag micro powder foaming material doped with mesoporous material and preparation method of lithium slag micro powder foaming material

Through the preparation method of mesoporous materials, combined with lithium slag micropowder and silicon micropowder, the problems of low strength and high thermal conductivity of lithium slag-based foaming materials are solved, and high porosity, low thermal conductivity and low cost lithium slag micropowder are achieved. Foaming material has excellent fire resistance, thermal insulation and moisture resistance.

CN119118140AInactive Publication Date: 2024-12-13SICHUAN HUHUI SURVEYING & DESIGN CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411272011.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium slag-based foaming materials have low overall strength and high thermal conductivity, and have problems such as weak lithium slag absorption capacity, easy to cause secondary pollution, lack of technical performance and high cost.

Method used

The preparation method of mesoporous materials is adopted to adjust the pH value by stirring alkaline silica sol with water and surfactant to form a composite wet gel, and heat and dry in anhydrous ethanol to prepare mesoporous materials and combine lithium slag Micropowder, silicon powder and foaming agent are used to prepare lithium slag micropowder foaming materials with high porosity and low thermal conductivity.

Benefits of technology

It improves the overall strength and porosity of the material, reduces the thermal conductivity, reduces production costs, and adjusts the material density and has excellent fire resistance, thermal insulation and moisture resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118140A_ABST
    Figure CN119118140A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a mesoporous material, foamed aggregate, a mesoporous material-doped lithium slag micro-powder foamed material and a preparation method of the mesoporous material-doped lithium slag micro-powder foamed material, and belongs to the technical field of environmental substitute materials. Specific lithium slag is ground to a certain specific surface area and then mixed with silica powder and a mesoporous material, and then a binding agent, a fiber material, an exciting agent and a foaming agent are added according to a certain sequence; and the foaming material with uniform pores, firmness and light weight is obtained by fully stirring and adopting a physical and chemical combined foaming mode. The foaming material is environment-friendly and low in cost, and various properties of the foaming material are better than those of materials in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental substitute materials, and specifically relates to a preparation method of a mesoporous material, a foaming aggregate, and a lithium slag micropowder foaming material doped with the mesoporous material and a preparation method thereof. Background Art

[0002] Lithium slag is a solid waste discharged after the lithium element is purified from mineral raw materials such as spodumene, lithium mica, and lithium aluminum phosphate through crushing, calcination (950-1000℃), acid leaching, and neutralization. Its main components are silicon dioxide, aluminum oxide, and calcium carbonate, with a small amount of sulfur oxides, phosphorus oxides, magnesium oxides, iron oxides, and titanium oxides. Therefore, lithium slag has a certain volcanic ash effect and is a water-hardening solid waste. The Si in the lithium slag powder after grinding and excitation is 4+ 、Al 3+ , Ca 2+ The plasma hydration rate is faster, and it spontaneously forms gel systems such as silica (-si-o-si-), silica aluminum (-si-o-al-), calcium silicate (csh), calcium aluminate (ash), and ettringite (aft, afm). The gel structures inside the material fit each other, and the physical strength of the gel material is improved.

[0003] At present, the main method of using lithium slag to prepare foaming materials is to use lithium slag and other easily hydrated materials to stimulate its gelling properties. The prior art discloses a solid waste-based composite lithium slag ultrafine admixture and its preparation method and application, which is used to replace 8-12% of cement clinker in cement mortar; the prior art also discloses a room temperature curing foam insulation board containing silica hydrophobic material and its preparation method, wherein the hydrophobic silica hydrophobic material dosage is 10-20%.

[0004] With the continuous expansion of upstream and downstream industries in my country's lithium industry, the amount of lithium slag emissions has increased year by year. In the existing technology, the development of lightweight thermal insulation materials based on lithium slag has problems such as weak lithium slag absorption capacity, secondary pollution caused by lithium slag absorption process, lack of technical performance of lithium slag products, and high actual application cost of lithium slag products. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a method for preparing a mesoporous material, a foamed aggregate, and a lithium slag micropowder foamed material doped with a mesoporous material and a preparation method thereof, which solves the problem of low overall strength and high overall thermal conductivity of the foamed material in the prior art.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a mesoporous material comprising the following steps:

[0007] S1: mixing alkaline silica sol and water, stirring at a speed of 100-500 r / min for 15-30 min, then adding a surfactant and stirring at 40-70° C. for 15-30 min to obtain solution 1; the pH of the alkaline silica sol is 9-11, and the silicon dioxide content is 20-40wt%; the mass ratio of the alkaline silica sol, water and surfactant is 1:4:0.03;

[0008] S2: Add 0.5-2 mol / L dilute hydrochloric acid to solution 1 at a stirring speed of 160-300 r / min, adjust the pH to 2.86-6.5, and obtain solution 2;

[0009] S3: Add 0.5-2 mol / L ammonium hydroxide dilute solution to solution 2 at a stirring speed of 160-300 r / min, adjust the pH to 8-12, and let the solution stand for 1-2 hours after a milky white opaque colloid appears in the solution to obtain a composite wet gel;

[0010] S4: Place the composite wet gel into a mold and add anhydrous ethanol, then heat at 55-75°C for 4 hours. Remove the anhydrous ethanol in the mold and continue drying at 55-75°C for 30-50 hours. Then adjust the temperature to 40-80°C and dry for 72 hours. De-mold and grind to obtain the mesoporous material.

[0011] The beneficial effects of the present invention are as follows: the silicon source for preparing the mesoporous material of the present invention is an inorganic silicon source, and there is no need to use highly polluting, volatile organic solvents in the preparation process, while the silica hydrophobic material is expensive, the manufacturing process is cumbersome, and a large amount of volatile organic solvents and modifiers that are harmful to the environment are used in the hydrophobic modification process. The porosity of the traditional silica hydrophobic material is 80-95%, and the thermal conductivity is 0.033-0.070W / (m·K). The porosity of the foaming material obtained by the mesoporous material provided by the present invention is 79.09-97.17%, and the thermal conductivity is 0.036-0.069W / (m·K). When the high porosity and low thermal conductivity similar to those of the traditional silica hydrophobic material are achieved, the production material cost is only 1 / 10-1 / 15 of the hydrophobic material.

[0012] Based on the above technical solution, the present invention can also be improved as follows.

[0013] The present invention also discloses a foamed aggregate, which comprises the following components by weight: 70-90 parts of lithium slag powder, 6.3 parts of 800-1200 mesh silicon powder, 3.7-23.7 parts of mesoporous material, 0.3 parts of foaming agent, 0.2 parts of calcium silicate, 0.2 parts of activator and 0.5 parts of binder; the foamed aggregate is prepared by the following steps:

[0014] Mix the raw materials according to their mass proportions, and stir at a speed of 80 to 120 r / min for 10 to 15 minutes to obtain foamed aggregate.

[0015] Furthermore, the specific surface area of ​​lithium slag powder is 550-1000m 2 / kg, the components of the lithium slag powder are as follows by mass percentage: SiO2≥47.27%, Al2O3≥22.21%, CaO≥8.56%, and SO3≤15.94%.

[0016] Furthermore, the foaming agent is one or more of aluminum powder, sodium bicarbonate, calcium carbonate, silicon carbide, sodium dodecyl sulfate, animal keratin foaming agent, plant protein foaming agent, polyvinyl alcohol, calcium stearate, and polyacrylamide.

[0017] Furthermore, the activator is one or more of water glass, anhydrous sodium sulfate, sodium hydroxide, calcium hydroxide, aluminum sulfate 18hydrate, and triethanolamine.

[0018] Furthermore, the binder is one or more of aluminum dihydrogen phosphate, phosphoric acid, alkaline silica sol, water, and polycarboxylate water reducer.

[0019] The beneficial effects of the present invention are as follows: the present invention uses the waste powder after the treatment of spodumene, consumes a large amount of lithium slag, and greatly improves the overall strength of the material. Compared with the cement binder commonly used in the traditional slag solidification treatment, the present invention utilizes the bonding effect of (-o-si-o-) bonds produced by the polycondensation reaction of alkaline silica sol, which is not only conducive to improving the bonding ability of the siliceous components in the material, but also supplements the calcium silicate (csh), calcium aluminate (ash), calcium sulfonate (Aft, Afm) and other gelling systems generated by the self-hydration of amorphous silicon dioxide, aluminum oxide and calcium oxide in the lithium slag micropowder, thereby improving the overall strength; on the other hand, the high pH of the alkaline silica sol is conducive to the Si in the material. 4+ 、Al 3+ , Ca 2+The dissolution of ions increases the reaction rate, forming a corresponding gel and thus improving the early strength. Compared with traditional materials, the use of alkaline silica sol as a binder and silica powder as a filler material not only makes the overall grading of the material more reasonable, but also makes the microstructure more uniform. After doping with mesoporous materials, firstly, the growth of Ca(OH)2 lamellar hydrated crystals is inhibited, the average size of its crystals at the microscopic scale is reduced, and the development of cracks caused by the growth of lamellar weak crystals is reduced; secondly, the growth of calcium sulfonate crystals is restricted and fixed, and the micro-expansion effect of calcium sulfonate crystals is reduced in physical space, so that the filling and bonding effects of columnar and needle-shaped calcium sulfonate crystals can be effectively exerted; thirdly, thanks to the three-dimensional pore microstructure of the mesoporous material, it can be used as a lightweight micro-filler without increasing the apparent density of the material, so that the overall porosity of the foamed material is increased by 20% to 30%, and its compressive strength is increased compared with that without adding mesoporous materials; fourthly, the mesoporous material is evenly dispersed in the aqueous gelling system, and in the process of pore generation, it acts as a containing material of the bubble wall to enhance the structural strength, and forms microscopic foaming nuclei after the addition of the foaming agent, so that the bubbles inside the material are more uniform, which plays a role in adjusting the bubble distribution and bubble diameter.

[0020] The present invention also discloses a lithium slag micropowder foaming material doped with a mesoporous material, which comprises the following raw materials, measured by mass: 100 parts of foaming aggregate, 1 to 3 parts of aluminum silicate fiber powder, 10 to 15 parts of water, 45 to 55 parts of a binder, 0.1 to 0.3 parts of an activator, 0.15 parts of a soluble starch and 5 to 6 parts of a composite foaming agent.

[0021] Furthermore, the composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, with a stirring speed of 5 to 15 r / min and a stirring time of 3 to 5 min.

[0022] The beneficial effects of the present invention are as follows: the present invention is based on the lithium slag foamed aggregate doped with mesoporous materials, and the prepared foamed material has a uniform pore structure and a high porosity of 79.09-97.17%; the thermal conductivity is 0.036-0.069W / (m·K), which is only half of the traditional ALC board; the density of the material can be adjusted in the range of 360-500kg / m according to different proportions 3 The compressive strength is 2.5-6.5 MPa, which is 2-3 MPa higher than that of traditional ALC boards, and it has excellent fire resistance, heat preservation and moisture resistance.

[0023] The present invention also discloses a method for preparing a lithium slag micropowder foaming material doped with a mesoporous material, which is prepared by the following steps:

[0024] S1: Mix aluminum silicate fiber powder, water, binder, activator and soluble starch according to mass fractions, and stir at 600-700 r / min for 10-15 min to obtain a mixture 1;

[0025] S2: Mix the mixture 1 with the foamed aggregate and stir at a speed of 60 r / min for 6 min to obtain the mixture 2, then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0026] S3: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 18-32°C, the curing pressure is normal pressure, and the curing time is 30-40h. After curing, demoulding is completed.

[0027] Furthermore, the viscosity coefficient of the second mixture is less than or equal to 1.55 Pa.s.

[0028] The beneficial effects of the present invention are: the preparation method provided by the present invention is simple and easy to implement, easy to produce, and has excellent industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a technical flow chart;

[0030] Figure 2 This is the XRD pattern of lithium slag powder. DETAILED DESCRIPTION

[0031] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0032] Example 1

[0033] A mesoporous material is prepared by the following steps:

[0034] S1: 1 part by mass of alkaline silica sol (PH ≥ 9, silicon dioxide content of 30wt%) was stirred and mixed with 4 parts by mass of water at room temperature, with a stirring speed of 300r / min and a mixing time of 25min; after being uniformly mixed, 0.03 parts by mass of lauramide propyl betaine amphoteric surfactant was added, and the mixed solution was heated to 55°C and stirred for 25min until the solution turned light blue, to obtain solution 1;

[0035] S2: Add 1.25 mol / L dilute hydrochloric acid to solution 1 at a stirring speed of 240 r / min, adjust the pH to 5, and stir for 2 h to obtain solution 2;

[0036] S3: Add 1.25 mol / L ammonium hydroxide dilute solution to solution 2 at a stirring speed of 240 r / min, adjust the pH to 10, stir for 30 min, and let stand for 1.5 h after a milky white opaque colloid appears in the solution to obtain a composite wet gel;

[0037] S4: Place the composite wet gel into a mold and add anhydrous ethanol, then heat at 65°C for 4 hours. Remove the anhydrous ethanol in the mold and continue drying at 65°C for 40 hours. Then adjust the temperature to 70°C and dry for 72 hours. De-mold and grind into 450 mesh powder to obtain mesoporous material 1.

[0038] Example 2

[0039] A mesoporous material is prepared by the following steps:

[0040] S1: 1 part by mass of alkaline silica sol (PH≥11, silica content of 20wt%) was stirred and mixed with 4 parts by mass of water at room temperature, with a stirring speed of 100r / min and a mixing time of 30min. After being mixed evenly, 0.03 parts by mass of lauramide propyl betaine amphoteric surfactant was added, and the mixed solution was heated to 40°C and stirred for 30min until the solution turned light blue, to obtain solution 1;

[0041] S2: Add 0.5 mol / L dilute hydrochloric acid to solution 1 at a stirring speed of 300 r / min, adjust the pH to 2.86, and stir for 3 h to obtain solution 2;

[0042] S3: Add 2 mol / L ammonium hydroxide dilute solution to solution 2 at a stirring speed of 300 r / min, adjust the pH to 12, stir for 45 min, and let stand for 1 h after a milky white opaque colloid appears in the solution to obtain a composite wet gel;

[0043] S4: Place the composite wet gel into a mold and add anhydrous ethanol, then heat at 55°C for 4 hours. Remove the anhydrous ethanol in the mold and continue drying at 55°C for 50 hours. Then adjust the temperature to 40°C and dry for 72 hours. De-mold and grind into 400 mesh powder to obtain mesoporous material 2.

[0044] Example 3

[0045] A mesoporous material is prepared by the following steps:

[0046] S1: 1 part by mass of alkaline silica sol (PH≥10, silica content of 40wt%) was stirred and mixed with 4 parts by mass of water at room temperature, with a stirring speed of 500r / min and a mixing time of 125min. After the mixture was evenly mixed, 0.03 parts by mass of lauramide propyl betaine amphoteric surfactant was added, and the mixed solution was heated to 70°C and stirred for 15min until the solution turned light blue, thereby obtaining solution 1;

[0047] S2: Add 2 mol / L dilute hydrochloric acid to solution 1 at a stirring speed of 160 r / min, adjust the pH to 6.5, and stir for 1 h to obtain solution 2;

[0048] S3: Add 0.5 mol / L ammonium hydroxide dilute solution to solution 2 at a stirring speed of 160 r / min, adjust the pH to 8, stir for 15 min, and let stand for 2 h after a milky white opaque colloid appears in the solution to obtain a composite wet gel;

[0049] S4: Place the composite wet gel into a mold and add anhydrous ethanol, then heat at 75°C for 4 hours. Remove the anhydrous ethanol in the mold and continue drying at 75°C for 30 hours. Then adjust the temperature to 80°C and dry for 72 hours. De-mold and grind into 400 mesh powder to obtain mesoporous material three.

[0050] Example 4

[0051] A foamed aggregate, calculated by weight, comprising the following raw materials: a specific surface area of ​​700m 2 / kg lithium slag powder 90 parts, 1000 mesh silicon powder 6.3 parts, mesoporous material 3.7 parts, polyvinyl alcohol 0.3 parts, calcium silicate 0.2 parts, anhydrous sodium sulfate 0.2 parts, polycarboxylate water reducer 0.5 parts; foamed aggregate is prepared by the following steps:

[0052] The raw materials were mixed according to their mass proportions and stirred at a speed of 100 r / min for 12 min to obtain foamed aggregate 1.

[0053] Example 5

[0054] A foamed aggregate, calculated by weight, comprising the following raw materials: a specific surface area of ​​550m 2 / kg lithium slag powder 85 parts, 800 mesh silicon powder 6.3 parts, mesoporous material II 8.7 parts, polyvinyl alcohol 0.3 parts, calcium silicate 0.2 parts, anhydrous sodium sulfate 0.2 parts, polycarboxylate water reducer 0.5 parts; the foamed aggregate is prepared by the following steps:

[0055] The raw materials were mixed according to their mass proportions and stirred at a speed of 80 r / min for 15 min to obtain foamed aggregate II.

[0056] Example 6

[0057] A foamed aggregate, calculated by weight, comprising the following raw materials: a specific surface area of ​​1000m 2 / kg lithium slag powder 80 parts, 1200 mesh silicon powder 6.3 parts, mesoporous material three 13.7 parts, polyvinyl alcohol 0.3 parts, calcium silicate 0.2 parts, anhydrous sodium sulfate 0.2 parts, polycarboxylate water reducer 0.5 parts; foamed aggregate is prepared by the following steps:

[0058] The raw materials were mixed according to their mass proportions and stirred at a speed of 120 r / min for 10 min to obtain foamed aggregate three.

[0059] Example 7

[0060] A foamed aggregate, calculated by weight, comprising the following raw materials: a specific surface area of ​​700m 2 / kg lithium slag powder 75 parts, 1000 mesh silicon powder 6.3 parts, mesoporous material 18.7 parts, polyvinyl alcohol 0.3 parts, calcium silicate 0.2 parts, anhydrous sodium sulfate 0.2 parts, polycarboxylate water reducer 0.5 parts; foamed aggregate is prepared by the following steps:

[0061] The raw materials were mixed according to their mass proportions and stirred at a speed of 100 r / min for 12 min to obtain foamed aggregate 4.

[0062] Example 8

[0063] A foamed aggregate, calculated by weight, comprising the following raw materials: a specific surface area of ​​700m 2 / kg lithium slag powder 70 parts, 1000 mesh silicon powder 6.3 parts, mesoporous material 23.7 parts, polyvinyl alcohol 0.3 parts, calcium silicate 0.2 parts, anhydrous sodium sulfate 0.2 parts, polycarboxylate water reducer 0.5 parts; foamed aggregate is prepared by the following steps:

[0064] The raw materials were mixed according to their mass proportions and stirred at a speed of 100 r / min for 12 min to obtain foamed aggregate No. 5.

[0065] Example 9

[0066] A lithium slag micropowder foaming material doped with mesoporous material, comprising the following raw materials by weight: 100 parts of foaming aggregate, 2 parts of aluminum silicate fiber powder, 12.4 parts of water, 49.6 parts of binder, 0.2 parts of triethanolamine, 0.15 parts of soluble starch and 5.4 parts of composite foaming agent; wherein the composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, and is prepared by stirring at a speed of 10r / min for 4 minutes; the preparation process of the lithium slag micropowder foaming material doped with mesoporous material is as follows Figure 1 As shown, it is prepared by the following steps:

[0067] S1: Mix aluminum silicate fiber powder, water, binder, activator and soluble starch according to mass fractions, and stir at 650 r / min for 12 min to obtain mixture 1;

[0068] S2: Mix material 1 and foamed aggregate 1 and stir at a speed of 60 r / min for 6 min to obtain a mixture 2 (viscosity coefficient ≤ 1.55 Pa.s), then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0069] S4: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 25°C, the curing pressure is normal pressure, and the curing time is 35 hours. After curing, demoulding is completed.

[0070] Example 10

[0071] A lithium slag micropowder foaming material doped with mesoporous material, which is composed of the following raw materials by mass: 100 parts of foaming aggregate 2, 1 part of aluminum silicate fiber powder, 15 parts of water, 45 parts of alkaline silica sol, 0.3 parts of triethanolamine, 0.15 parts of soluble starch and 5 parts of composite foaming agent, wherein the composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, and is stirred at a speed of 15r / min for 3 minutes; the preparation process of the lithium slag micropowder foaming material doped with mesoporous material is as follows Figure 1 As shown, it is prepared by the following steps:

[0072] S1: Aluminum silicate fiber powder, water, binder, activator and soluble starch are mixed according to mass fractions, and stirred at 600 r / min for 15 min to obtain a mixture 1;

[0073] S2: Mix material 1 and foamed aggregate 2 and stir at a speed of 60 r / min for 6 min to obtain a mixture 2 (viscosity coefficient ≤ 1.55 Pa.s), then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0074] S4: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 18°C, the curing pressure is normal pressure, and the curing time is 40 hours. After curing, demoulding is completed.

[0075] Embodiment 11

[0076] A lithium slag micropowder foaming material doped with a mesoporous material is composed of the following raw materials by mass: 100 parts of foaming aggregate 3, 3 parts of aluminum silicate fiber powder, 10 parts of water, 55 parts of alkaline silica sol, 0.1 parts of triethanolamine, 0.15 parts of soluble starch and 6 parts of a composite foaming agent, wherein the composite foaming agent is a mixture of hydrogen peroxide and an animal keratin foaming agent in a mass ratio of 12.5:1, and is stirred at a speed of 5 r / min for 5 minutes; the preparation process of the lithium slag micropowder foaming material doped with a mesoporous material is as follows Figure 1 As shown, it is prepared by the following steps:

[0077] S1: Mix aluminum silicate fiber powder, water, binder, activator and soluble starch according to mass fractions, and stir at 700 r / min for 10 min to obtain mixture 1;

[0078] S2: Mix material 1 and foamed aggregate 3 and stir at a speed of 60 r / min for 6 min to obtain a mixture 2 (viscosity coefficient ≤ 1.55 Pa.s), then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0079] S4: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 32°C, the curing pressure is normal pressure, and the curing time is 30 hours. After curing, demoulding is completed.

[0080] Example 12

[0081] A lithium slag micropowder foaming material doped with mesoporous material, comprising the following raw materials by weight: 100 parts of foaming aggregate 4, 2 parts of aluminum silicate fiber powder, 12.4 parts of water, 49.6 parts of alkaline silica sol, 0.2 parts of triethanolamine, 0.15 parts of soluble starch and 5.4 parts of composite foaming agent; wherein the composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, and is prepared by stirring at a speed of 10r / min for 4 minutes; the preparation process of the lithium slag micropowder foaming material doped with mesoporous material is as follows Figure 1 As shown, it is prepared by the following steps:

[0082] S1: Mix aluminum silicate fiber powder, water, binder, activator and soluble starch according to mass fractions, and stir at 650 r / min for 12 min to obtain mixture 1;

[0083] S2: Mix material 1 and foamed aggregate 4 and stir at a speed of 60 r / min for 6 min to obtain a mixture 2 (viscosity coefficient ≤ 1.55 Pa.s), then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0084] S4: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 25°C, the curing pressure is normal pressure, and the curing time is 35 hours. After curing, demoulding is completed.

[0085] Example 13

[0086] A lithium slag micropowder foaming material doped with mesoporous material, comprising the following raw materials by weight: 100 parts of foaming aggregate, 2 parts of aluminum silicate fiber powder, 12.4 parts of water, 49.6 parts of alkaline silica sol, 0.2 parts of triethanolamine, 0.15 parts of soluble starch and 5.4 parts of composite foaming agent; wherein the composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, and is prepared by stirring at a speed of 10r / min for 4 minutes; the preparation process of the lithium slag micropowder foaming material doped with mesoporous material is as follows Figure 1 As shown, it is prepared by the following steps:

[0087] S1: Mix aluminum silicate fiber powder, water, binder, activator and soluble starch according to mass fractions, and stir at 650 r / min for 12 min to obtain mixture 1;

[0088] S2: Mix material 1 and foamed aggregate 5 and stir at a speed of 60 r / min for 6 min to obtain a mixture 2 (viscosity coefficient ≤ 1.55 Pa.s), then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0089] S4: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 25°C, the curing pressure is normal pressure, and the curing time is 35 hours. After curing, demoulding is completed.

[0090] Comparative Example 1

[0091] A foamed aggregate, calculated by weight, comprising the following raw materials: a specific surface area of ​​700m 2 / kg lithium slag powder 90 parts, 1000 mesh silicon powder 6.3 parts, polyvinyl alcohol 0.3 parts, calcium silicate 0.2 parts, anhydrous sodium sulfate 0.2 parts, polycarboxylate water reducer 0.5 parts; the foamed aggregate is prepared by the following steps:

[0092] The raw materials were mixed according to their mass proportions and stirred at a speed of 100 r / min for 12 min to obtain a comparative foamed aggregate.

[0093] Comparative Example 2

[0094] A lithium slag micropowder foaming material is composed of the following raw materials, measured by mass: 100 parts of comparative foaming aggregate, 2 parts of aluminum silicate fiber powder, 12.4 parts of water, 49.6 parts of alkaline silica sol, 0.2 parts of triethanolamine, 0.15 parts of soluble starch and 5.4 parts of composite foaming agent; wherein the composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, and is stirred at a speed of 10 r / min for 4 minutes; the lithium slag micropowder foaming material doped with mesoporous material is prepared by the following steps:

[0095] S1: Mix aluminum silicate fiber powder, water, binder, activator and soluble starch according to mass fractions, and stir at 650 r / min for 12 min to obtain mixture 1;

[0096] S2: Mix the mixture 1 with the comparative foamed aggregate and stir at a speed of 60 r / min for 6 min to obtain the mixture 2 (viscosity coefficient ≤ 1.55 Pa.s), then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product;

[0097] S4: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 25°C, the curing pressure is normal pressure, and the curing time is 35 hours. After curing, demoulding is completed.

[0098] Experimental Example 1

[0099] Lithium slag powder composition analysis: The lithium slag powder used in the present invention is the waste powder of lithium mica lithium slag or spodumene lithium slag after grinding process, and its specific surface area is ≥550m 2 / kg; the lithium slag powder was analyzed using an X-ray diffractometer. The results are as follows Figure 2 As shown, its main components are SiO2, Al2O3, SO3, CaO, P2O5, MgO, Fe2O3, TiO2, and the mass percentages of the main components are shown in Table 1.

[0100] Table 1 Main components of lithium slag powder

[0101]

[0102] Experimental Example 2

[0103] The performance of the lithium slag micropowder foamed materials doped with mesoporous materials prepared in Examples 9 to 13 and Comparative Example 2 was tested. The test results are shown in Table 2.

[0104] Table 2 Performance index comparison table

[0105]

[0106]

[0107] The lithium slag micropowder foamed material doped with mesoporous material of the present invention has a uniform structure. The addition of mesoporous material increases the overall porosity of the foamed material by 20% to 30%, while the compressive strength is increased relative to that without adding mesoporous material. The thermal conductivity of Examples 9 to 13 is 0.036-0.069 W / (m·K), which is significantly lower than that of the lithium slag micropowder foamed material without mesoporous material doped in Comparative Example 2. The density of the material can be adjusted in the range of 360-500 kg / m according to different ratios. 3 .

[0108] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing a mesoporous material, characterized in that: The following steps are involved: S1: mixing alkaline silica sol and water, stirring at a speed of 100-500 r / min for 15-30 min, then adding a surfactant and stirring at 40-70° C. for 15-30 min to obtain solution 1; the alkaline silica sol has a pH of 9-11 and a silicon dioxide content of 20-40 wt %; the mass ratio of the alkaline silica sol, water and surfactant is 1:4:0.03; S2: Add 0.5-2 mol / L dilute hydrochloric acid to solution 1 at a stirring speed of 160-300 r / min, adjust the pH to 2.86-6.5, and stir for 1-3 h to obtain solution 2; S3: Add 0.5-2 mol / L ammonium hydroxide dilute solution to solution 2 at a stirring speed of 160-300 r / min, adjust the pH to 8-12, stir for 15-45 min, and let stand for 1-2 h after a milky white opaque colloid appears in the solution to obtain a composite wet gel; S4: Place the composite wet gel into a mold and add anhydrous ethanol, then heat at 55-75°C for 4 hours. Remove the anhydrous ethanol in the mold and continue drying at 55-75°C for 30-50 hours. Then adjust the temperature to 40-80°C and dry for 72 hours. De-mold and grind to obtain the mesoporous material.

2. A foamed aggregate, characterized in that: The raw materials are as follows, calculated by weight: 70-90 parts of lithium slag powder, 6.3 parts of 800-1200 mesh silicon powder, 3.7-23.7 parts of the mesoporous material prepared by the preparation method according to claim 1, 0.3 parts of a foaming agent, 0.2 parts of calcium silicate, 0.2 parts of an activator and 0.5 parts of a binder.

3. The foamed aggregate according to claim 2, characterized in that: The specific surface area of ​​the lithium slag powder is 550-1000m 2 / kg, the components of the lithium slag powder are as follows by mass percentage: SiO2≥47.27%, Al2O3≥22.21%, CaO≥8.56%, and SO3≤15.94%.

4. The foamed aggregate according to claim 2, characterized in that: The foaming agent is one or more of aluminum powder, sodium bicarbonate, calcium carbonate, silicon carbide, sodium dodecyl sulfate, animal keratin foaming agent, plant protein foaming agent, polyvinyl alcohol, calcium stearate, and polyacrylamide.

5. The foamed aggregate according to claim 2, characterized in that: The activator is one or more of water glass, anhydrous sodium sulfate, sodium hydroxide, calcium hydroxide, aluminum sulfate 18hydrate, and triethanolamine.

6. The foamed aggregate according to claim 2, characterized in that: The binder is one or more of aluminum dihydrogen phosphate, phosphoric acid, alkaline silica sol, water, and polycarboxylate water reducer.

7. A lithium slag micropowder foaming material doped with mesoporous material, characterized in that: The raw materials include the following, calculated by mass: 100 parts of the foamed aggregate according to any one of claims 2 to 6, 1 to 3 parts of aluminum silicate fiber powder, 10 to 15 parts of water, 45 to 55 parts of a binder, 0.1 to 0.3 parts of an activator, 0.15 parts of a soluble starch and 5 to 6 parts of a composite foaming agent.

8. The lithium slag micropowder foaming material doped with mesoporous material according to claim 7, characterized in that: The composite foaming agent is a mixture of hydrogen peroxide and animal keratin foaming agent in a mass ratio of 12.5:1, with a stirring speed of 5 to 15 r / min and a stirring time of 3 to 5 min.

9. The method for preparing the lithium slag micropowder foamed material doped with mesoporous material according to claim 7 or 8, characterized in that: Prepared by the following steps: S1: Aluminum silicate fiber powder, water, a binder, an activator and soluble starch are mixed according to mass fractions, and stirred at 600-700 r / min for 10-15 min to obtain a mixture 1; S2: Mix the mixture 1 with the foamed aggregate and stir at a speed of 60 r / min for 6 min to obtain the mixture 2, then add the composite foaming agent to the mixture 2, adjust the stirring speed to 360 r / min, and continue stirring for 15 s to obtain a crude product; S3: Pour the crude product into a mold and sprinkle water for curing. The curing temperature is 18-32°C, the curing pressure is normal pressure, and the curing time is 30-40h. After curing, demoulding is completed.

10. The method for preparing the lithium slag micropowder foamed material doped with mesoporous material according to claim 9, characterized in that: The viscosity coefficient of the second mixture is less than or equal to 1.55 Pa.s.

Citation Information

Cited By

  • Lithium slag composite admixture, low-carbon lithium slag concrete and preparation method of low-carbon lithium slag concrete

    CN119707335A